Development and Validation of a Critical Thinking Skills Instrument for Grade 11 Biology Students Based on Ennis’s Framework - Try Susanti; Dwi Gusfarenie; Nanda Gusriani; Diandara Oryza; Nining Nuraida (International Journal of Education and Teaching Zone, 2026)
The ability to think critically is a key competency required of students in the 21st century, particularly in science education. This study aimed to develop and empirically evaluate a critical thinking skills assessment instrument for Grade 11 senior high school students in biology learning. The instrument was developed using the ADDIE development model, encompassing the analysis, design, development, implementation, and evaluation stages. Empirical testing was conducted during the implementation stage with Grade 11 senior high school students in Jambi City. Item analysis was performed to examine content validity, empirical validity, reliability, item difficulty, and discrimination indices. Empirical data were analyzed using ANATES version 4.0.9. The results indicated that 22 out of 56 items met the predefined validation criteria, demonstrating acceptable levels of item difficulty and discrimination power. The reliability coefficient of the finalized instrument was 0.68, which is considered acceptable for an exploratory educational assessment instrument. These findings suggest that the developed instrument possesses adequate psychometric properties for measuring students’ critical thinking skills in biology learning and can support future instructional evaluation and research within similar educational contexts.